The Role of Criminal Law in Providing Restitution for Victims of Money Laundering: Problems and Prospects - Antonius P. S. Wibowo (GoAcademica Research & Publishing, 2026)
This article examines the role of criminal law in granting restitution to victims of Money Laundering offenses within Indonesia’s criminal justice system, focusing on implementation challenges and future prospects under recent legal reforms. Although restitution is legally recognized as a victim’s right, its realization has been significantly delayed, as reflected in finalized court decisions in the Indosurya and Viralblast cases, where restitution has not yet been effectively distributed. This study analyzes juridical and institutional factors contributing to these delays and evaluates prospects for strengthening restitution enforcement under Law Number 1 of 2023 concerning the Criminal Code and Law Number 20 of 2025 concerning the Criminal Procedure Code. Using a normative-conceptual legal approach based on statutory regulations, court judgments, and Lawrence Friedman's legal system theory, the study identifies weak coordination between law enforcement authorities and the Witness and Victim Protection Agency, as well as the absence of clear coordination mechanisms in the previous procedural framework, as central obstacles. The findings indicate that recognizing restitution as an additional penalty and introducing coordination provisions in the new procedural regime provide a stronger normative basis for enforcement. The article concludes that effective restitution depends on harmonizing legal substance, institutional structure, and legal culture.